An Analysis of Moral Values in Justice League Movie - Eni Wijayanti; Dyah Nugrahani; Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar, Universitas PGRI Semarang, 2023)
This final project studied the analysis of the moral values in “Justice Leagu” Movie. This research focused mainly on the moral values found in the movie. The objectives of the study were (1) to find out the moral values found in Justice League Movie, (2) to explore the moral values reflected in main character of Justice League Movie.The design of the research was descriptive qualitative research. The object of the research were script Justice League Movie. The instruments of the study were the data from the script movie. This discussions from prior chapters are to be summarized to achieve the purpose of the study. First, the moral values of being there were peace and ability, self confident and potencially, courage sake and kindness, and the last one is honestly. The second, the moral values of giving were justice and mercy, love and affection, kindness and friendsliness, and the last one is respect.The dominant types of moral values of being use in Justice League movie were peace and ability and selfconfident and potencially that have same percentage that was 35,71%. Second the moral values of giving the dominant was love and affection 75%.